2018
DOI: 10.1002/ajmg.a.40525
|View full text |Cite
|
Sign up to set email alerts
|

Ablepharon and craniosynostosis in a patient with a localized TWIST1 basic domain substitution

Abstract: The TWIST family is a group of highly conserved basic helix–loop–helix transcription factors. In humans, TWIST1 haploinsufficiency causes Saethre–Chotzen syndrome, which is characterized by craniosynostosis. Heterozygous localized TWIST1 and TWIST2 basic domain substitutions exert antimorphic effects to cause Sweeney–Cox syndrome, Barber–Say syndrome, and ablepharon‐macrostomia syndrome, respectively. Sweeney–Cox syndrome, Barber–Say syndrome, and ablepharon‐macrostomia syndrome share the facial features of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Previous findings, including the data from this study, demonstrated that Twist1 cko/mice have severe craniofacial deformities, including exencephaly, severe mandibular hypoplasia, and a lack of frontonasal and maxillary bone (Bildsoe et al, 2009;Firulli et al, 2007;Vincentz et al, 2008). In humans, haploinsufficiency of TWIST1 leads to the syndromic form of craniosynostosis and cleft palate (Kunz and Fritz, 1999;Seto et al, 2007;Takenouchi et al, 2018). It has been shown that Twist1-deficient mesenchymal cells do not have mesenchymal characteristics as observed in mouse chimeras created from wild type embryos injected with Mtwist deficient embryonic stem cells (Chen and Behringer, 1995), and that Twist1 is essential for CNCC survival to give rise to CNCC-derived craniofacial formation as shown by an increased level of mesenchymal apoptosis in Twist1 cko/- (Bildsoe et al, 2013;Chen et al, 2007;Zhang et al, 2012).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Previous findings, including the data from this study, demonstrated that Twist1 cko/mice have severe craniofacial deformities, including exencephaly, severe mandibular hypoplasia, and a lack of frontonasal and maxillary bone (Bildsoe et al, 2009;Firulli et al, 2007;Vincentz et al, 2008). In humans, haploinsufficiency of TWIST1 leads to the syndromic form of craniosynostosis and cleft palate (Kunz and Fritz, 1999;Seto et al, 2007;Takenouchi et al, 2018). It has been shown that Twist1-deficient mesenchymal cells do not have mesenchymal characteristics as observed in mouse chimeras created from wild type embryos injected with Mtwist deficient embryonic stem cells (Chen and Behringer, 1995), and that Twist1 is essential for CNCC survival to give rise to CNCC-derived craniofacial formation as shown by an increased level of mesenchymal apoptosis in Twist1 cko/- (Bildsoe et al, 2013;Chen et al, 2007;Zhang et al, 2012).…”
Section: Discussionsupporting
confidence: 51%
“…Twist1 expression is maintained in the cranial neural crest-derived mesenchyme of the frontonasal and pharyngeal processes (Bildsoe et al, 2009;Fuchtbauer, 1995). In humans, mutations in TWIST1 cause Saethre-Chotzen syndrome, characterized by craniosynostosis and cleft palate, Sweeney-Cox syndrome, and Robinow-Sorauf syndrome (Kunz and Fritz, 1999;Takenouchi et al, 2018;Seto et al, 2007). In mice, Twist1 is crucial for neural tube closure and CNCC-derived craniofacial bone and cartilage formation as reported in the phenotypes of Twist1 null and conditional knockout (CKO) in CNCCs (Chen et al, 2007;Bildsoe et al, 2013;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that changes to the local meningeal environment are sufficient to disrupt the growth and remodeling of mLVs in craniosynostosis. The model we have chosen for our current analysis is overall more affected than what is typically observed in humans, and shows similarities with Sweeney-Cox syndrome, a severe craniofacial disorder caused by dominant-negative mutations in TWIST1 (Kim et al, 2017; Takenouchi et al, 2018). However, homozygous Twist1 FLX/FLX :Sm22a-Cre animals model venous malformations that are absent in heterozygous Twist1 FLX/WT :Sm22a-Cre animals, the latter of which more closely mimic skull phenotypes found in humans (Tischfield et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Human phenotypes related to Sweeney-Cox syndrome involve the facial nerves of the central nervous system. [ 18 ] We thus further posit that CFAP47 may act in a particular region of the nervous system such that CFAP47 mutations can cause abnormal facial development, thereby promoting hemifacial atrophy.…”
Section: Discussionmentioning
confidence: 99%